2005
DOI: 10.1074/jbc.m412479200
|View full text |Cite
|
Sign up to set email alerts
|

Anion-independent Iron Coordination by the Campylobacter jejuni Ferric Binding Protein

Abstract: Campylobacter jejuni, the leading cause of human gastroenteritis, expresses a ferric binding protein (cFbpA) that in many pathogenic bacteria functions to acquire iron as part of their virulence repertoire. Recombinant cFbpA is isolated with ferric iron bound from Escherichia coli. The crystal structure of cFbpA reveals unprecedented iron coordination by only five protein ligands. The histidine and one tyrosine are derived from the N-terminal domain, whereas the three remaining tyrosine ligands are from the C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 45 publications
0
44
0
1
Order By: Relevance
“…An exception is the Fbp from Yersinia enterocolitica, which has five protein-derived ligands and a coordinated water molecule (38). It has been suggested that the class III proteins represent the earliest forms of Fbps from which proteins with modified iron sites and different synergistic anion-binding requirements have evolved (33). FutA1 and FutA2 have been assigned to this class, and for the former this has been confirmed by the crystal structure of the protein (36).…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…An exception is the Fbp from Yersinia enterocolitica, which has five protein-derived ligands and a coordinated water molecule (38). It has been suggested that the class III proteins represent the earliest forms of Fbps from which proteins with modified iron sites and different synergistic anion-binding requirements have evolved (33). FutA1 and FutA2 have been assigned to this class, and for the former this has been confirmed by the crystal structure of the protein (36).…”
mentioning
confidence: 84%
“…The class III Fbp from Campylobacter jejuni (cFbpA) reportedly binds Fe(II), which is subsequently oxidized to Fe(III) (33). It has recently been suggested that both FutA1 and FutA2 favor Fe(II), with hardly any detectable Fe(III) binding and that this preference is likely to extend to all class III Fbps (36).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our present investigation involves the study of multiple iron(III) binding to apo-nFbpA using iron citrates as the metal source. Based on a wild-type variant of FbpA isolated from Bordetella pertussis, [28,29] we have also studied the apo-nFbpA and H9Y-nFbpA fitted using a single-site binding model. The theoretical fit of the data suggests either that four iron ions are bound to a single-site or that four iron atoms are bound to four identical sites, and that the binding reaction is exothermic.…”
Section: Resultsmentioning
confidence: 99%